#### Answer

Correct

#### Work Step by Step

$7x-(x+2)=7x-x-2\rightarrow$ apply distributive property
$7x-x-2=7x-x-2$

Published by
Pearson

ISBN 10:
0321955048

ISBN 13:
978-0-32195-504-3

Correct

$7x-(x+2)=7x-x-2\rightarrow$ apply distributive property
$7x-x-2=7x-x-2$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.